Gender Role Representation in Hollywood Action Cinema: A Comparative Analysis of Blade Runner (1982) and the Avengers (2012) - Michala Michala (Universitas Airlangga, 2026)
Blade Runner (1982) and The Avengers (2012) are separated by thirty years, yet both cast women in roles that appear, on the surface, physically formidable. This study compares gender representation across both films along four dimensions: characterization, fighting style, costume, and image representation. Through qualitative textual analysis and a comparative framework, drawing on Butler's theory of gender performativity and role typology from Tasker, Gilpatric, and Inness as primary analytical instruments, the study finds that the most significant representational shifts have occurred at the narrative and costume levels, while the physical homogeneity of female characters remains unchanged across the thirty-year interval. This suggests that progress in gender representation is hierarchical — more achievable at the level of narrative than at the level of how the female body is visually constructed.